A Proposed Combination of Formal and Entrepreneurial Approaches to Strategy Creation: A Multi-Case Study Approach - Chegini, Hooshang Nezamivand; Hosseini, Sayed Mahmood (Journal of Asian Business Strategy, 2020)
The purpose of this paper is to evaluate and optimize the current approaches to strategic planning in certain Iranian companies. To this means, it tries to define the effectiveness circumstances of formal approaches for creating a strategy in the selected companies. The present research is a developmental study. The purpose of the r, it is developmental research. It is an exploratory study in terms of purpose. Questions of study will be answered in the course of the data were collected from interviews, personal experiences, historical documents, and questionnaire. The research follows a case-based research methodology in which multiple-case study design and analysis is used to help establish cross-case conclusions and the development of policy implications for future research in the work. For this purpose, 6 performance measures are used. The population comprised of two leading Iranian companies. In addition, two less successful finally, interviewing leaders of organizations and distributing questionnaires and using the participation of more than 120 senior and middle managers of the organizations, their strategy creation approaches are identified. The findings of the study reveal that successful companies tend to implement a mixture of formal and entrepreneurial approaches to create strategies.